Efektivitas Bantuan Langsung Tunai terhadap Ekonomi Masyarakat Miskin Saat Pandemi (Studi Kasus Pekon Panggungrejo Utara Kecamatan Sukoharjo Kabupaten Pringsewu, Lampung) - Lintang Nurmalasari; Muhammad Husaini (Journal on Education, 2023)
COVID-19 is a pandemic that began in 2019 and caused problems in the health and economic sectors. Declining economic conditions resulted in an increase in the number of poor people during the pandemic. The government has allocated Direct Cash Assistance (BLT) to help poor people who are experiencing difficulties during the pandemic. This study used descriptive qualitative method. There are two types of research data, namely primary data and secondary data. This study uses documentation, interviews, questionnaires, and observations to obtain data. The purpose of this study was to look at the effectiveness of BLT on the economy of the poor during a pandemic by distributing questionnaires to 71 respondents with the results of the study namely, direct cash assistance in Pekon Panggungrejo Utara had been carried out very effectively.